Falciparum but not vivax malaria increases the risk of hypertensive disorders of pregnancy in women followed prospectively from the first trimester - Harrington, Whitney E. (BMC Med, 2021)
BACKGROUND: Malaria and hypertensive disorders of pregnancy (HDoP) affect millions of pregnancies worldwide, particularly those of young, first-time mothers. Small case-control studies suggest a positive association between falciparum malaria and risk of pre-eclampsia but large prospective analyses are lacking. METHODS: We characterized the relationship between malaria in pregnancy and the development of HDoP in a large, prospectively followed cohort. Pregnant women living along the Thailand-Myanmar border, an area of low seasonal malaria transmission, were followed at antenatal clinics between 1986 and 2016. The relationships between falciparum and vivax malaria during pregnancy and the odds of gestational hypertension, pre-eclampsia, or eclampsia were examined using logistic regression amongst all women and then stratified by gravidity. RESULTS: There were 23,262 singleton pregnancies in women who presented during the first trimester and were followed fortnightly. Falciparum malaria was associated with gestational hypertension amongst multigravidae (adjusted odds ratio (AOR) 2.59, 95%CI 1.59–4.23), whereas amongst primigravidae, it was associated with the combined outcome of pre-eclampsia/eclampsia (AOR 2.61, 95%CI 1.01–6.79). In contrast, there was no association between vivax malaria and HDoP. CONCLUSIONS: Falciparum but not vivax malaria during pregnancy is associated with hypertensive disorders of pregnancy.